Investigating spectroscopic measurement of sublingual veins and tissue to estimate central venous oxygen saturation - Sircan-Kucuksayan, Aslinur; Eray, Oktay; Buyukaksu, Murat; Gumus, Birce; Dursun, Oguz; Canpolat, Murat (Technology and health care, 2022)
BACKGROUND: Venous oxygen saturation reflects venous oxygenation status and can be used to assess treatment and prognosis in critically ill patients. A novel method that can measure central venous oxygen saturation (ScvO 2 ) non-invasively may be beneficial and has the potential to change the management routine of critically ill patients. OBJECTIVE: The study aims to evaluate the potential of sublingual venous oxygen saturation (SsvO 2 ) to be used in the estimation of ScvO 2 . METHODS: We have developed two different approaches to calculate SsvO 2 . In the first one, near-infrared spectroscopy (NIRS) measurements were performed directly on the sublingual veins. In the second approach, NIRS spectra were acquired from the sublingual tissue apart from the sublingual veins, and arterial oxygen saturation was measured using a pulse oximeter on the fingertip. RESULTS: Twenty-six healthy subjects were included in the study. In the first and second approaches, average SsvO 2 values were 75.0% ± 1.8 and 75.8% ± 2.1, respectively. The results of the two different approaches were close to each other and similar to ScvO 2 of healthy persons ( > 70%). CONCLUSION: Oxygen saturation of sublingual veins has the potential to be used in intensive care units, non-invasively and in real-time, to estimate ScvO 2 .